In Silico Study of Torch Ginger Flower (Etlingera elatior (Jack) R.M.Sm. flos) Bioactive Compounds Targeting TGF-β Receptor Type I (TGF-βR1) as Potential Tumor Suppressor Agents - Yohana Faustine Yuarsa; Garneta Izzati Herdy Putri; Valeri Belliana Sanjaya; Akmal Taufiqur Rahman; Shela Salsabila; Nawadhir Fauzan; Muchtaridi Muchtaridi (Indonesian Society for Cancer Chemoprevention, 2025)
Cancer remains one of the leading causes of death worldwide, with an estimated 16.3 million cancer-related deaths projected by 2040. Current cancer therapies still face various challenges such as resistance, toxicity, and high costs, highlighting the need for more targeted approaches in the discovery of new therapies. Torch ginger flower (Etlingera elatior (Jack) R.M.Sm. flos) has been reported to contain bioactive compounds with potential tumor-suppressive activities through modulation of cancer-related pathways. However, in silico evidence evaluating its active compounds as potential inhibitors of transforming growth factor-beta receptor type I (TGF-βR1), a protein involved in tumor proliferation and metastasis remains limited. This study aimed to predict and evaluate the potential of Etlingera elatior compounds as tumor-suppressing agents targeting TGF-βR1 using computational approaches. Lipinski’s Rule of Five and ADME-Tox predictions were performed to assess drug-likeness and pharmacokinetic properties, while pharmacophore screening and molecular docking were conducted to identify hit compounds and predict their binding affinities. Among the tested compounds, kaempferol and quercetin showed the highest pharmacophore fit scores (47.21% and 47.07%, respectively) and the best binding affinities to TGF-βR1 (-7.98 kcal/mol; Ki 1.42 μM for kaempferol and -7.87 kcal/mol; Ki 1.72 μM for quercetin), and although their binding poses were not the most similar to the reference inhibitor LY3200882 (-8.39 kcal/ mol; Ki 0.71 μM), the consistent alignment of favorable pharmacophore fit and binding energy still reinforces their potential. These findings indicate that kaempferol and quercetin have promising potential as candidate natural tumor-suppressive agents targeting TGF-βR1.Keywords: Cancer, TGF-βR1, Torch Ginger Flower, Molecular Docking.